Multicenter, prospective, open-label, observational study of bimatoprost 0.01% in patients with primary open-angle glaucoma or ocular hypertension - Laube T (Dove Medical Press, 2012)
Stefan Pfennigsdorf,1 Osman Ramez,2 Gerrit von Kistowski,3 Birgit Mäder,4 Peter Eschstruth,5 Michael Froböse,6 Ulrich Thelen,7 Christoph Spraul,8 Dietmar Schnober,9 Hazel Cooper,10 Thomas Laube111Polch Ophthalmology Practice, Polch, 2Buxtehude Ophthalmology Practice, Buxtehude, 3Nürnberg Ophthalmology Practice, Nürnberg, 4Weißwasser Ophthalmology Practice, Weißwasser, 5Ophthalmology Practice, Kiel, 6Ophthalmology Practice, Bielefeld, 7Group Practice, Münster, 8Group Practice, Ulm, 9Ophthalmology Practice, Werdohl, Germany; 10Allergan, Marlow, UK, 11Group Practice, Düsseldorf, GermanyBackground: Bimatoprost 0.01% was developed for improved tolerability over bimatoprost 0.03%, while maintaining efficacy in lowering intraocular pressure (IOP). This multicenter, prospective, open-label, observational study was designed to investigate the efficacy and tolerability of bimatoprost 0.01% in routine clinical practice.Methods: Data were collected from 10,337 patients with primary open-angle glaucoma or ocular hypertension attending 1334 centers in Germany. The primary efficacy outcome was mean change in IOP in each eye from baseline to 10–14 weeks after initiation of bimatoprost 0.01%. Target IOP, prior therapies, additional treatments, and adverse events were also assessed. All treatment decisions were at the physicians’ discretion.Results: Bimatoprost 0.01% significantly lowered mean IOP from baseline by –4.1 mmHg (P < 0.0001) in all patients after a mean of 10.45 weeks. In patients without previous treatment, bimatoprost 0.01% reduced mean IOP from baseline by –6.5 mmHg (P < 0.0001). Bimatoprost 0.01% also significantly reduced IOP in patients previously treated with monotherapy of β-blockers, prostaglandin analogs, carbonic anhydrase inhibitors or bimatoprost 0.03%. No adverse events were reported by 93.9% of patients during treatment with bimatoprost 0.01%; the most commonly reported adverse events were eye irritation (2.0%), ocular hyperemia (1.4%), and conjunctival hyperemia (1.2%). Physicians and patients rated tolerability and adherence as high, and most patients said they would continue with bimatoprost 0.01% treatment.Conclusion: Bimatoprost 0.01% can produce additional IOP-lowering effects when used in routine clinical practice in patients who have received prior therapy, in addition to lowering IOP in previously untreated patients. A high rate of continuation of therapy with bimatoprost 0.01% was observed in patients who switched from a variety of different medications. The results suggest that bimatoprost 0.01% is a suitable first-choice therapy in patients with primary open-angle glaucoma or ocular hypertension.Keywords: bimatoprost 0.01%, glaucoma, observational, ocular hypertension, intraocular pressure